1996
DOI: 10.1152/ajplung.1996.271.3.l484
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone suppresses mucus production and MUC-2 and MUC-5AC gene expression by NCI-H292 cells

Abstract: Excessive production of airway mucus is a characteristic feature of many chronic inflammatory lung diseases. Although current pharmacological approaches to excessive mucus production are limited, glucocorticoids appear to be the most effective among a few useful drugs. The exact evidence for the effectiveness of glucocorticoids on mucus production has not been fully elucidated to date. The purpose of this study is to clarify the effect of dexamethasone on mucus production and mucin gene expression in a human p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 0 publications
5
56
0
2
Order By: Relevance
“…Pretreatment with 40 M of quercetin and 20 M of EGCG decreased mucin gene expression, and cell proliferation was not influenced at any of the concentrations. These results agree with the suppression of MUC2 and MUC5AC expression by dexamethasone in NCI-H292 cells 14 and that of IL-1␤-induced MUC2/5AC expression and mucin production by budesonide. 21,22 Our results also agree with other studies on the suppression of the mucin gene by [6]-gingerol and EGCG.…”
Section: Discussionsupporting
confidence: 90%
“…Pretreatment with 40 M of quercetin and 20 M of EGCG decreased mucin gene expression, and cell proliferation was not influenced at any of the concentrations. These results agree with the suppression of MUC2 and MUC5AC expression by dexamethasone in NCI-H292 cells 14 and that of IL-1␤-induced MUC2/5AC expression and mucin production by budesonide. 21,22 Our results also agree with other studies on the suppression of the mucin gene by [6]-gingerol and EGCG.…”
Section: Discussionsupporting
confidence: 90%
“…Since airway inflammation is key to the development of mucus hypersecretion [44], the inhibitory actions of budesonide may not be entirely unexpected. In addition, direct effects of glucocorticosteroids on mucin gene expression have been reported in vitro [45]. In combination with the results obtained using tiotropium bromide, these data indicate that glucocorticosteroids and anticholinergic drugs may both be effective in preventing remodelling of mucus-producing cells in allergic airways disease.…”
Section: Discussionmentioning
confidence: 52%
“…Kai et al (44) showed that dexamethasone suppressed mucin release directly from a lung carcinoma cell line, most likely as a result of inhibition of mucin synthesis. Kim et al showed that cationic peptides such as eosinophil major basic protein (45) and poly-L-lysine and poly-L-arginine (46) suppress mucin release from primary hamster TSE cells without cytotoxicity.…”
Section: Agents That Regulate Airway Goblet Cell Mucin Releasementioning
confidence: 99%